Pengaruh Model Pembelajaran dan Minat Terhadap Hasil Belajar Siswa MA - Hizbi, Tsamarul; Wajdi, Badrul; Fartina, Fartina; Mardiah, Siti (Universitas Hamzanwadi, 2023)
This study aimed to determine (1) the effect of the Two Stay Two Stray (TSTS) and Numbered Head Together (NHT) learning models on learning outcomes, (2) The effect of high and low learning interest on physics learning outcomes, (3) Interaction between models Two Stay Two Stray (TSTS) and Numbered Head Together (NHT) types with interest in learning about physics learning outcomes. Thetype of research used was quantitative research. The populations in this study were all class XI IPA MA NWDI Pancor as many as 2 classes. While the sample used in this study was non-probability sampling technique. The sample in this study was XI IPA 2 as an experimental class using the NHT learning model. Then, XI IPA 1 as a control class using the TSTS learning model. The research design used was 2x2 factorial design. Thedata collection techniques used was questionnaire and test. After that the data wereanalyzed using two-way ANOVA. The conclusions of this study were (1) there was an effect of cooperative learning model type Two Stay Two Stray (TSTS) and Numbered Head Together (NHT) on student physics learning outcomes on elasticity material. Based on the results of further tests, it was found that students who were taught using the Numbered Head Together (NHT) method gave better average results compared to students who were taught using the Two Stay Two Stray (TSTS) method with F-count > F-table. 4,52 > 4, 14, (2) There was an influence between students who had high interest in learning and students who had low interest in learning on student learning outcomes. Based on the further test, it was found that students who had high interest had better average results than students who had low interest. Students who had a high interest were more active and enthusiastic in learning activities with F-count > F-table 4.75 > 4.14, (3) There was no interaction between the Two Stay Two Stray (TSTS) and Numbered Head Together (NHT) type models with interest in learning on the physics learning outcomes of students of class XI IPA MA NWDI Pancor on elasticity material. Based on the results of hypothesis testing conducted using two-way ANOVA, it was found that F-count < F-table with F-count < F-table. 0.61 > 4.14.